2017
DOI: 10.1155/2017/3846236
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pyrotechnic Shock Sources for Shear Type Explosive Bolt

Abstract: To identify the shock generated sources of shear type explosive bolt, five kinds of explosive bolts with different states, including high preload, low preload, no preload, no piston shear, and only propellant combustion, were designed. The decoupling of four kinds of shock sources, including the collision of propellant combustion, piston shear weak surface, end of piston stroke, and preload release, was realized. Their acceleration responses at 15 cm from the shock source center on 60 cm × 60 cm × 1 cm equival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…All of the material structural parameters were from the AUTODYN material library, and their specific values are listed in Tables 2-5 [19][20][21][22].…”
Section: Shock and Vibrationmentioning
confidence: 99%
“…All of the material structural parameters were from the AUTODYN material library, and their specific values are listed in Tables 2-5 [19][20][21][22].…”
Section: Shock and Vibrationmentioning
confidence: 99%
“…Reducing the energetic material mass is acknowledged as one of the most effective ways, but this solution leads to performance degradation of the gas generator. 12,13 Some investigations suggested using the method of absorbing shock by utilizing honeycomb materials with high shock resistance, 14,15 and other investigations 16 confirmed that honeycomb composites had superior buffer performance than traditional materials. Zhang et al 17 and Ma et al 18 developed new damping materials, such as metal rubber and shape memory alloys, which are now widely used in the field of launch dynamics.…”
mentioning
confidence: 95%
“…Researchers have proposed a range of strategies to decrease the effect of the shock response based on these previous investigations. Reducing the energetic material mass is acknowledged as one of the most effective ways, but this solution leads to performance degradation of the gas generator 12,13 . Some investigations suggested using the method of absorbing shock by utilizing honeycomb materials with high shock resistance, 14,15 and other investigations 16 confirmed that honeycomb composites had superior buffer performance than traditional materials.…”
Section: Introductionmentioning
confidence: 99%
“…An explosive bolt is a simple, highly reliable, and efficient pyrotechnic release device widely used in the aerospace industry [1,2]. Various types of explosive bolts have been designed, including "ridge-cut" [3,4], fragmenting-type [5], piston-type [6,7], shear-type [8,9], and shear pin-type explosive bolts [10], among others. e action of explosive bolts inevitably induces high-frequency and highamplitude transient shock, known as pyroshock, which rarely causes structure failure.…”
Section: Introductionmentioning
confidence: 99%